2014
DOI: 10.1128/aem.01001-14
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate-Associated Acid Resistance in Bacteria

Abstract: dGlucose confers acid resistance on exponentially growing bacteria by repressing formation of the cyclic AMP (cAMP)-cAMP receptor protein (CRP) complex and consequently activating acid resistance genes. Therefore, in a glucose-rich growth environment, bacteria are capable of resisting acidic stresses due to low levels of cAMP-CRP. Here we reveal a second mechanism for glucose-conferred acid resistance. We show that glucose induces acid resistance in exponentially growing bacteria through pyruvate, the glycolys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…Crp has been reported to regulate the expression of the general stress response regulator RpoS of E . coli 40 . We demonstrated that loss of rpoS rendered P .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Crp has been reported to regulate the expression of the general stress response regulator RpoS of E . coli 40 . We demonstrated that loss of rpoS rendered P .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, rpoS transcription was demonstrated to be regulated by Crp-cAMP 56 , and Crp could inhibit RpoS expression through Spf, an Hfq-dependent sRNA that facilitates acid resistance by activating RpoS expression in E . coli 40 . Our unpublished data also revealed that P .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cellular toxicity attributed to pyruvate under acid stress is controversial. While some studies point to a beneficial role for intracellular pyruvate following acidic stress, others have alluded to a more toxic nature for this metabolite (Harvey & Collins, 1963;Tsau et al, 1992;Repizo et al, 2011;Wu et al, 2014). Hence, to test whether intracellular pyruvate affects S. aureus under acidic stress, we challenged the wild-type strain with increasing concentrations of sodium pyruvate in Tryptic Soy broth (TSB) that was acidified to an initial pH of 4.5 and monitored growth at a wavelength of 600 nm (OD 600 ) for 24 h. Because of the weak acid properties of pyruvic acid (pKa5 2.49), this approach not only allows a small percentage (<1%; estimate based on the Henderson-Hasselbalch equation) of extracellular pyruvic acid to diffuse freely into cells and ensure cytoplasmic acidification, but also simultaneously increases the levels of intracellular pyruvate (upon disassociation of pyruvic acid within the cytoplasm) in the acid stressed cells.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, a recent report demonstrated that hydrogen peroxide stress in Pseudomonas fluorescens provoked a metabolic reprogramming that enhanced the production of pyruvate . Pyruvate also induces acid resistance in bacteria by the expression of the small noncoding RNAs, which in turn activates expression of RpoS .…”
Section: Resultsmentioning
confidence: 99%